Graphene-Wrapped Hybrid Spheres of Electrical Conductivity - Ju, Sang Ah; Kim, Kyunghee; Kim, Jung-Hyun; Leet, Sang-Soo (American Chemical Society, 2011)
We present a simple approach for the fabrication of monoisperse electroconductive hybrid spheres using graphene sheet-wrapping via ionic interaction-based self-assembly. The graphene sheets partially charged with anion, which were prepared by controlled chemical reduction of graphite oxide, were mixed with monodisperse polymer nanospheres containing cationic surface charge to form ionic self-assembled hybrid spheres of core shell structure. The resulting graphene-wrapped hybrid spheres were found to have graphene layer thickness of ca. 10 nm and to exhibit electrical conductivity of 1.33-4.21 S/m as well as monodisperse distributions in shape and diameter.
Keywords: GRAPHITE OXIDE; AQUEOUS DISPERSIONS; REDUCTION; NANOCOMPOSITES; MICROSPHERES; ELECTRONICS